CONVECTIVE DRYING CHARACTERISTICS OF EGGPLANT SLICES - Doymaz, Ibrahim; Gol, Esin (WILEY-BLACKWELL, 2011)
The effects of air temperature and sample thickness on the drying kinetics of blanched/unblanched eggplant slices were investigated. Eggplant slices were dried as single layers with thicknesses of 0.5 and 1 cm in the range of 50-80C of drying air temperature in a cabinet dryer. Moisture transfer from eggplant slices was described by applying Fick's diffusion model. The values of effective diffusivity varied from 0.93 x 10(-10) to 8.84 x 10(-10) m(2)/s, depending on drying conditions. Effective diffusivity values increased with increasing temperature. The temperature dependence of the effective diffusivity was found to follow the Arrhenius relationship. The values of activation energy (Ea) varied from 20.12 to 30.83 kJ/mol for blanched/unblanched eggplant slices. A nonlinear regression procedure was used to fit two semi-theoretical models available in the literature to the experimental moisture loss data. The models were compared based on the coefficient of determination, the reduced chi-square and the root mean square error between the observed and predicted moisture ratios. The Page model was found to be most suitable in describing the drying characteristics of eggplant slices.
Keywords: SWEET-POTATO SLICES; RED BELL PEPPER; HOT-AIR; KINETICS; L.; STORAGE; MODEL; DEHYDRATION; PARAMETERS; BEHAVIOR; Engineering; Food Science & Technology